Physiological Stress in Rescued Wild Koalas Are Influenced by Habitat Demographics, Environmental Stressors, and Clinical Intervention - Narayan, Edward; Vanderneut, Tayla (Frontiers in Endocrinology, 2019)
Koalas are rescued from the wild often with incidence of burns from bushfire, injury from animal attacks, vehicle collision and diseases. Exposure to environmental stressors (trauma and disease) could generate physiological stress and potentially impact the outcomes of clinical management intervention and rehabilitation of rescued wild koalas. It is important to quantify the stress physiology of wild koalas upon registering into clinical care. This study demonstrates the first report of physiological stress assessment in rescued wild koalas (n = 22) to determine the potential influences of habitat-specific demographics, stressor category and clinical diagnosis. Faecal samples were collected from the koalas at rescue and routinely during hospitalization to provide a longitudinal assessment of the koala’s stress response throughout clinical care. Faecal glucocorticoid metabolites (FCM) enzyme-immunoassay was used to index physiological stress non-invasively. Koalas were admitted with exposure to various categories of environmental trauma such as vehicle collision, dog attack, burns from forest fire (this also related to conditions such as copious drinking and flat demeanour), and other injury. The main disease diagnosed was chlamydial infections. In terms of environmental interactions, it was found that habitat-specific demographics, location where the rescued koala was found, especially the rural-urban fringe, influenced FCM levels. Furthermore, there was significant interaction between location, stressor category and clinical diagnosis for mean FCM levels. However, these factors were not predictive of the clinical outcome (euthanised or released). Overall, the results provide invaluable insights into how wild koalas respond physiologically to environmental trauma and disease and how methods of care, husbandry and treatment can be used to further reduce the impacts of stress with the ultimate aim of increasing the rehabilitation and future release of rescued koalas to revive the declining mainland populations.